Development of Character Education Models in Madrasas Through the Establishment of the Tahajud Prayer - Supendi, Pepen; Palah; Hasanah, Aan (Jurnal Pendidikan Agama Islam, 2020)
This study aimed to examine and explore the development of student character education models through habituation of programmed tahajud prayers in MTs As-Sa'idah. This research uses a qualitative approach with descriptive methods. Data collection techniques are interviews, observation, and study of literature. The results of this study, are: First, the reality of education in the inheritance of the values ​​of character education through the process of habituating the programmed prayer; Second, the tahajud prayer is a character inheritance model that is able to preserve the values ​​of the Sunnah of the Prophet Muhammad. The inheritance model of character education through habituation of tahajud prayer are: 1) focus, derived from the doctrine of the Qur'an and Sunnah; 2) Procedure, using a direct learning model. And the Third, the character values ​​that can be implemented as a basis for character building show in 9 of character values.